PENGURANGAN RACUN AMONIA, BAHAN ORGANIK DAN PADATAN TERSUSPENSI DI MEDIA BUDIDAYA UDANG GALAH DENGAN BIOFILTER DARI BAHAN GENTENG PLASTIK BERGELOMBANG - Muslim, Muslim (Bumi Lestari, 2013)
Abstract Fish culture and shrimp culture has been developing rapidly during the last few decades, it is due to the increase of fish and shrimps demand. Increasing aquaculture activities especially with semi-intensive and intensive system have significant effect on waste production, which has to be removed or to be reduced quickly because will effect on fish in rearing tank and environment when through away to environment such as river and sea. The objective of this study was to know the capability of corrugated plastic to remove or to reduce ammonia, organic matter and Suspended Solids (SS). The result of the study showed that the concentration of ammonia, organic matter and SS in waste water reduced after were passed to corrugated plastic tank. Reducing of ammonia, organic matter and SS that occurred in shrimps rearing tank for culturing shrimp with treatment different protein concentration contain in meal fish were 32% and 28% with removal efficiency for ammonia were 10.95% and 14.37%; organic matter 49.02% and 19.94%; SS were 35.46% and 22.22%. This treatment can minimize increasing rate of ammonia, organic matter and SS, thus this treatment can maintain water quality in rearing tank. So, it can be concluded that corrugated plastic had capability to reduce or remove of ammonia, organic matter and SS.
Keywords: Keywords: Corrugated plastic; removal efficiency, ammonia; organic matter, suspended solids